2022
DOI: 10.1021/acs.iecr.1c04380
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Fundamental Understanding of Geological Hydrogen Storage

Abstract: Geological H 2 storage plays a central role to enable the successful transition to the renewable H 2 economy and achieve net-zero emission in the atmosphere. Depleted oil and gas reservoirs are already explored with extensive reservoir and operational data. However, residual hydrocarbons can mix with injected H 2 in the reservoirs. Furthermore, low density and high diffusivity of H 2 may establish H 2 leakage from the reservoirs via fault pathways. Interestingly, H 2 can be consumed by microorganisms, which re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(65 citation statements)
references
References 224 publications
(378 reference statements)
1
63
1
Order By: Relevance
“…Renewable energy resources (solar, wind, biomass, and waves) are considerably affected by the seasonal fluctuation of atmospheric parameters (e.g., temperature, sunshine, and wind force), which when coupled with changing energy demand, can lead to renewable energy excesses or deficits (Abe et al., 2019). As such, it will not be possible to balance the supply with demand of a wholly renewable energy system without large‐scale storage (Aftab et al., 2022; Muhammed et al., 2022; Osman et al., 2021). Energy storage solutions ensure efficiency, flexibility, and security of the energy system.…”
Section: Introductionmentioning
confidence: 99%
“…Renewable energy resources (solar, wind, biomass, and waves) are considerably affected by the seasonal fluctuation of atmospheric parameters (e.g., temperature, sunshine, and wind force), which when coupled with changing energy demand, can lead to renewable energy excesses or deficits (Abe et al., 2019). As such, it will not be possible to balance the supply with demand of a wholly renewable energy system without large‐scale storage (Aftab et al., 2022; Muhammed et al., 2022; Osman et al., 2021). Energy storage solutions ensure efficiency, flexibility, and security of the energy system.…”
Section: Introductionmentioning
confidence: 99%
“…Additional experience of geological gas storage in porous rocks has been gained through the commercial operation of over 670 natural gas storage sites and over 30 carbon dioxide storage sites. 6 8 Published studies consider geological hydrogen storage to be technically feasible; however, several reviews have identified challenges which must be addressed to prove the safe containment and necessary recovery efficiencies of hydrogen in porous reservoirs. 3 , 9 13 The major barriers currently restricting the development of hydrogen storage are the following: (i) Hydrogen is characterized by a lower viscosity and higher mobility than natural gas and carbon dioxide.…”
mentioning
confidence: 99%
“…The rheology measurements (Figure 3) revealed that the base mud had an AV value of 18.7 cP, a PV of 8.8 cP, and a Figure 2: The H 2 S concentration in the outlet gas stream as a function of time. 4 Geofluids YP of 14.4 lb/100 ft 2 . The TRZM exhibited higher AV, PV, and YP values of 21 cP, 10 cP, and 17.9 lb/100 ft 2 , respectively.…”
Section: Rheology Measurementsmentioning
confidence: 99%
“…The presence of hydrogen sulfide (H 2 S) gas is a frequent problem encountered when drilling subsurface hydrocarbon formations. This gas is naturally found in oil and gas reservoirs and is formed either by geological or microbiological processes [1][2][3][4]. H 2 S invades the drilling system through either invading formations containing H 2 S-contaminated fluids, the metabolism of sulfate-reducing bacteria that survive in anaerobic conditions, or the thermal degradation of sulfur-containing drilling fluid additives [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%